The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1063/1.4961911
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced structural changes in a monomeric bacteriophytochrome

Abstract: Phytochromes sense red light in plants and various microorganism. Light absorption causes structural changes within the protein, which alter its biochemical activity. Bacterial phytochromes are dimeric proteins, but the functional relevance of this arrangement remains unclear. Here, we use time-resolved X-ray scattering to reveal the solution structural change of a monomeric variant of the photosensory core module of the phytochrome from Deinococcus radiodurans. The data reveal two motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 47 publications
(63 reference statements)
8
45
0
Order By: Relevance
“…This would be consistent with structural changes, refined against time-resolved X-ray scattering data for Dr BphP mon and for the full length Dr BphP. 27,28 The studies identified a twist and bending of the photosensory core 27 and an overall twist of the output domains with respect to PAS/GAF. 28 This is also consistent with how other sensory proteins are thought to work.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…This would be consistent with structural changes, refined against time-resolved X-ray scattering data for Dr BphP mon and for the full length Dr BphP. 27,28 The studies identified a twist and bending of the photosensory core 27 and an overall twist of the output domains with respect to PAS/GAF. 28 This is also consistent with how other sensory proteins are thought to work.…”
Section: Discussionsupporting
confidence: 64%
“…This indicates that the quaternary structure of Dr BphP mon is not changed dramatically upon photoactivation, which is consistent with the time-resolved solution scattering structures of the same protein fragment. 27 We also determined 15 N T1 and T2 relaxation times for each residue (Fig. 3a, b and SI Appendix, Fig.…”
Section: Residual Dipolar Couplings (Rdc) Indicate Changes In the Knomentioning
confidence: 99%
See 3 more Smart Citations